Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I am doing research, and while calculating a closed form expression, I got a form of integration like the following:

$$\int_{z=u}^{+\infty}\int_{t=u}^{+\infty}\frac{e^{-Az}}{z+B}\frac{te^{-tD}}{t-zC}dtdz$$ where $A$, $B$, $C$, $D$ and $u$ are positive reals.

I don't know if there is way to get the closed form of it or we have to rely on some approximations.

share|improve this question
add comment

1 Answer

$$\begin{align} \int_{z=u}^{+\infty}\int_{t=u}^{+\infty}\frac{te^{-tD}}{t-zC} \mathbb{d}t\mathbb{d}z &= \int_{z=u}^{+\infty} \left( \frac{e^{-Az}}{z+B} \int_{t=u}^{+\infty}\frac{te^{-tD}}{t-zC}\mathbb{d}t \right)\mathbb{d}z \\ &=\int_{z=u}^{+\infty} \left( \frac{e^{-Az}}{z+B} \underbrace{\int_{t=u}^{+\infty}\frac{te^{-tD}}{t-zC}\mathbb{d}t}_{J_{D,C}(u,z)} \right)\mathbb{d}z \\ \end{align}$$ with $$\begin{align} J_{D,C}(u,z) &= \int_{t=u}^{+\infty}\frac{te^{-tD}}{t-zC}\mathbb{d}t \\ &= \int_{t=u}^{+\infty}\frac{t-zC+zC}{t-zC}e^{-tD}\mathbb{d}t \\ &= \int_{t=u}^{+\infty}e^{-tD}\mathbb{d}t + zC\int_{t=u}^{+\infty}\frac{e^{-tD}}{t-zC}\mathbb{d}t\\ &= \left[\frac{e^{-tD}}{-D}\right]_u^{+\infty} + zC I_{D,zC}(u)\\ \end{align}$$

where $$I_{a,b}(u) = \int\limits_{u}^{\infty} \frac{\ \exp\left(-a t\right)}{t-b} \mathrm{d}t \stackrel{s=\frac{t-b}{u-b}}= (u-b)e^{-ab}\int\limits_{1}^{\infty} \frac{\ e^{-a(u-b)s}}{s} \mathrm{d}s =(u-b)e^{-ab}E_1(a(u-b))$$ $=>$ $$J_{D,C}(u,z) =\frac{e^{-uD}}{D} + zC(u-zC)e^{-zCD}E_1(D(u-zC))$$ Now :

$$\begin{align} \int_{z=u}^{+\infty}\int_{t=u}^{+\infty}\frac{te^{-tD}}{t-zC} \mathbb{d}t\mathbb{d}z &=\frac{e^{-uD}}{D}\int_{z=u}^{+\infty} \frac{e^{-Az}}{z+B} \mathbb{d}z + \int_{z=u}^{+\infty} \frac{zC(u-zC)e^{-zCD}E_1(D(u-zC))}{z+B} e^{-Az}\mathbb{d}z\\ &=\frac{e^{-uD}}{D}I_{A,-B} + \underbrace{\int_{z=u}^{+\infty} \frac{zC(u-zC)e^{-zCD}E_1(D(u-zC))}{z+B} e^{-Az}\mathbb{d}z}_{(1)}\\ \end{align}$$ Let $g(z)=(u-zc)De^{D(u-zC)}E_1(D(u-zC)) $
since $\frac{z}{z+B}= 1-\frac{B}{z+B}$ then : $$\begin{align} (1) &= \frac{C}{D}e^{-uD}\int_{z=u}^{+\infty}{g(z)} e^{-Az}\mathbb{d}z-\frac{BC}{D}e^{-uD}\int_{z=u}^{+\infty} \frac{g(z)}{z+B} e^{-Az}\mathbb{d}z \\ \end{align}$$

Consider the substitution $s=z-u$ $$\begin{align}(1) &= \frac{C}{D}e^{-uD}\int_{0}^{+\infty}{g(s+u)} e^{-As}\mathbb{d}s-\frac{BC}{D}e^{-uD}\int_{0}^{+\infty} \frac{g(s+u)}{z+B} e^{-As}\mathbb{d}s\\ &= \mathcal{L}\{g(s+u)\} (A) -\frac{BC}{D}e^{-uD}\mathcal{L}^2\{g(s+u)e^{-As}\} (B) \\ \end{align} $$ where $\mathcal{L}\{f(t)\}$ The Laplace transform and
$\mathcal{L}^2\{f(t)\}$ the second iterate of Laplace transform wich the same as the Stieltjes Transform given by: $\mathcal{S}\{f(x)\}(y)= \int_{0}^{+\infty} \frac{f(x)}{x+y} \mathbb{d}x$

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.